Synthesis of novel Zn0.5Mg0.5Fe2O4@TiO2 nanotube arrays with enhanced photoelectrocatalytic properties - Pan, J.; Li, Xin Yong; Zhao, Q.; Zhang, D. (Royal Society of Chemistry, 2015)
A novel nanocomposite electrode with tight and vertically aligned Zn0.5Mg0.5Fe2O4@TiO2 nanotube arrays (NTs) has been successfully synthesized via an ultrasonically assisted electrodeposition strategy. The scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD) of the composite nanostructures indicated that the as-prepared electrodes were well-aligned TiO2 NTs with Zn0.5Mg0.5Fe2O4 nanoparticles. The enhanced absorption of the nanocomposite electrode under simulated sun light and visible light regions were observed. The photoelectrochemical performance of the Zn0.5Mg0.5Fe2O4@TiO2 nanotube arrays showed excellent sensitive response to visible light. The surface-interface charge separation and transfer of photo-induced electrons and holes were also demonstrated by optical characterization. Meanwhile, the photoelectrochemical investigations clearly illustrated that the Zn0.5Mg0.5Fe2O4@TiO2 composite NTs had more effective photo-conversion capability than the unloaded TiO2 NTs. The saturated photocurrent density of the doped electrode was about 6.5 fold and 4 fold as high as that of the TiO2 NTs under the illumination of visible light and simulated sun light, respectively. In addition, the enhanced photoelectrocatalytic (PEC) ability of the as-prepared electrode was demonstrated in the degradation of toxic p-nitrophenol species. The much improved PEC activity can be attributed to both the visible-light photocatalytic activity of Zn0.5Mg0.5Fe2O4 and the heterostructure between Zn0.5Mg0.5Fe2O4 and TiO2.